Tuberculosis: A Common Infection with Rare Presentation, Isolated Sellar Tuberculoma with Panhypopituitarism - Agrawal, Vivek Mahesh (J Neurosci Rural Pract, 2019)
Isolated sellar tuberculoma is a very rare condition and usually presents with headache and decreased vision. It can present with panhypopituitarism with 3(rd) nerve palsy. Tuberculoma mimics pituitary adenoma clinically as well as radiologically and requires endoscopic transsphenoidal surgery and histopathological examination for the final diagnosis. We present a rare case of a 40-year-old female presented with headache, decreased vision, and unilateral 3(rd) nerve palsy with panhypopituitarism.